2009
DOI: 10.1142/s1793536909000217
|View full text |Cite
|
Sign up to set email alerts
|

Emd of Gaussian White Noise: Effects of Signal Length and Sifting Number on the Statistical Properties of Intrinsic Mode Functions

Abstract: This work presents a discussion on the probability density function of Intrinsic Mode Functions (IMFs) provided by the Empirical Mode Decomposition of Gaussian white noise, based on experimental simulations. The influence on the probability density functions of the data length and of the maximum allowed number of iterations is analyzed by means of kernel smoothing density estimations. The obtained results are confirmed by statistical normality tests indicating that the IMFs have non-Gaussian distributions. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…The shape of h(n) is largely dependent on the signal type, sampling rate, and noise power. This finding is counter to previous suggestions that the IMFs are Gaussian and Laplacian distributions [8]- [10].…”
Section: A Analysis Of Imf Probability Distributionscontrasting
confidence: 99%
See 2 more Smart Citations
“…The shape of h(n) is largely dependent on the signal type, sampling rate, and noise power. This finding is counter to previous suggestions that the IMFs are Gaussian and Laplacian distributions [8]- [10].…”
Section: A Analysis Of Imf Probability Distributionscontrasting
confidence: 99%
“…The statistical characteristics of the IMFs were previously investigated [8], [10], [11]. However, these investigations were limited to a comparison of the IMF distributions not an analysis of the EMD sifting process.…”
Section: A Analysis Of Imf Probability Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several investigations have been carried out in order to identify the effects of the EMD when applied to time series issued from various models, such as white, red, or fractional Gaussian noise, (Huang et al, 2003;Flandrin et al, 2004aFlandrin et al, , 2005Wu and Huang, 2004;Rilling et al, 2005;Schlotthauer et al, 2009;Colominas et al, 2012). As a result, it has been consistently shown that, irrespective of the assumed noise model, the EMD acts as an efficient wavelet-like dyadic filter, decomposing the stochastic inputs into IMFs having the same spectral shape but that are shifted in the frequency domain.…”
Section: Adaptive Background Null Hypothesismentioning
confidence: 99%
“…The influence of the signal length on the number of the IMFs and their statistics has been investigated in [19,20] on the basis of extensive simulations. For the corpora used in the experiment, the number of IMFs per speech frame log spectrum varies between 8 and 12.…”
Section: Empirical Mode Decomposition Algorithmmentioning
confidence: 99%